Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2009)
The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point; however, the lesions caused by B. corticola were longer in both oak species. On cork oak seedlings, all pathogens induced a signiﬁcant and gradual reduction in net photosynthesis and stomatal conductance values, whereas other physiological disturbances were induced only by B. corticola infections on holm oak seedlings.
Keywords: Cork oak; fungal pathogens; Holm oak; physiological responses (voyant); seedlings